Development of technology of obtaining raw materials for titanium alloys made of off-grade titanium sponge - Осипенко, Александр Викторович (Eastern-European Journal of Enterprise Technologies, 2015)
Simplification and efficiency improvement of the process of obtaining sintered products and semi-finished items made of sparingly alloyed titanium alloys with high mechanical properties are possible using titanium sponge with a given content of iron and oxygen. To study the method of obtaining titanium sponge with a given iron content in the process of screening and sieving, the pilot plant was designed and built. The iron concentration in titanium sponge was implemented in several ways by screening various sub-fractions of titanium sponge of a small fraction -2+0 mm. Industrial technology for titanium sponge production with a given iron content on the sponge screening plants was developed. Selection of parameters of the developed process: bulk material flow rate on the screen-table of the plant in the range 0.370...0.380 m/min at the material flow depth 9.0...11.0 mm, which provides the yield of the desired fraction of about 60% and the iron content of 1.50% (wt.) was made. Production technology of titanium sponge with a given chemical composition was implemented at the Zaporozhye Titanium and Magnesium Combine on the pilot plant for titanium sponge sieving, pilot unbalanced-throw screen 290 Gr with performance of 1000 kg/h. Sintered titanium billets of the alloy Ti-0,25O-1,5Fe were made of the manufactured product by hydrogenation, pressing and sintering of titanium sponge with a given chemical composition. The sintered alloy has a level of mechanical properties similar to that of serial sintered titanium alloys of grades 2M2A and PT5-1. Using titanium sponge with a given composition of alloying elements in combination with the powder metallurgy techniques of titanium alloys as a raw material for the production of sparingly alloyed sintered titanium alloys is economically advantageous and cost-effective due to eliminating a number of process operations and low cost of raw materials used.